THE OBSTRUCTION OF SEA POWER, THE RECOVER OF LAND POWER AND THE POSSIBILITY OF “INTERCONNECT POWER” - Xianming , Pan (PEOPLE: International Journal of Social Sciences, 2024)
Maritime versus land transportation, or the race between sea power and land power, is a topic that political scientists have been passionately discussing for centuries. In recent decades, sea power has undoubtedly prevailed. However, With the changes in the international political and economic situation and the frequent occurrence of wars and accidents (for example, the conflict in the Bab-el-Mandeb Strait and the backlog of goods in ports due to the epidemic), maritime transportation has been restricted at the present time. Coupled with the development and application of new technologies (examples include distributed photovoltaics, high-speed rail, ultra-high-voltage transmission technology and thorium-based nuclear power plants) and the rise of new economies, the rise of land power has become a new trend. In other words, “circulating power”, which combines sea power and land power, provides a new development perspective for human society. The interconnectedness of the world will beyond the “national center” perspective, bring about the well-being of mankind, and convert the struggle for power into economic cooperation and prosperity.